Producción, comercialización y rentabilidad de las empresas de lácteos y su relación con la economía del cantón La Maná, provincia de Cotopaxi, año 2011 - Rubio Chinga, Narcisa Elizabeth (2015)
This research work is based on production, marketing and profitability that perform large, medium and small dairy industries in Canton La Mana, period 2011. It began with a description of the main categories which enabled to know the theory from which the research starts off. For information gathering, the technique of surveying to producers in parishes Guasaganda, and Pucayacu, as well to middlemen and consumers of dairy products around Canton La Mana was applied; and according to the results it may be considered that the administration made by dairy producers is weak; also, taking in consideration the lack of technical expertise to facilitate efficient management of the business, which has influenced a limited business growth. To determine the profitability, three leading companies were chosen: Dairy products "La Finca" (Large Company)….